FOXM1 regulates proliferation, senescence and oxidative stress in keratinocytes and cancer cells - Smirnov, A; Panatta, E; Lena, A; Castiglia, D; Di Daniele, N; Melino, G; Candi, E (Impact Journals, 2016)
Several transcription factors, including the master regulator of the epidermis, p63, are involved in controlling human keratinocyte proliferation and differentiation. Here, we report that in normal keratinocytes, the expression of FOXM1, a member of the Forkhead superfamily of transcription factors, is controlled by p63. We observe that, together with p63, FOXM1 strongly contributes to the maintenance of high proliferative potential in keratinocytes, whereas its expression decreases during differentiation, as well as during replicative-induced senescence. Depletion of FOXM1 is sufficient to induce keratinocyte senescence, paralleled by an increased ROS production and an inhibition of ROS-scavenger genes (SOD2, CAT, GPX2, PRDX). Interestingly, FOXM1 expression is strongly reduced in keratinocytes isolated from old human subjects compared with young subjects. FOXM1 depletion sensitizes both normal keratinocytes and squamous carcinoma cells to apoptosis and ROS-induced apoptosis. Together, these data identify FOXM1 as a key regulator of ROS in normal dividing epithelial cells and suggest that squamous carcinoma cells may also use FOXM1 to control oxidative stress to escape premature senescence and apoptosis.